Spatial dynamics and modeling of wetlands degradation by remote sensing: The case of the small valley Adjarra in the lower valley of Ouémé (Ramsar Site No. 1018, south - east of Benin) - TCHIBOZO, ERIC ALAIN MAHUGNON (My University, 2014)
After registration of four of its wetlands to Ramsar sites for protecting them, Benin still experiencing a degradation of the environment across wetlands. Those in the lower valley of the Ouémé in general and the valley Adjarra in particular are under increasing anthropogenic pressure. The objective of this paper is to characterize the spatial dynamics and model the degradation of the valley Adjarra. The methodology is a geographical approach based on sampling, photo - digital interpretation, automatic detection and change mapping and modeling. The results show that the spatial dynamics of the landscape contributes to the degradation of the valley. It is characterized by the growth of urban areas (64.83%) of marshy grassland (619.18%), the gallery forest (249.00%), semi-deciduous forest (74.42%), plantations (231.18%), crops and fallow (516.14%), and regression of water (43.39%), dense forest (57.33%) and crops and fallow under palm trees (93.68%) now converted into plantations. The most important changes in the landscape are made in the dense forest and the least important in cultivated fields and fallow under palm trees. The increase in crop fields and fallows and agglomeration is regressive factors in dense forest. At the gallery forest and forest semi - deciduous, it is rather the regression occupancy rate of water and the crops and fallow land under palm trees behind the progression of these units. Thus, in the valley of Adjarra rate variation of vegetation is explained by changes in those of water, fields of crops and fallow crop fields and fallow under the palm trees and cities. This critical situation the degradation of the valley is particularly felt in the dense forest.
Keywords: wetlands; valley Adjarra; anthropogenic pressures; modeling; remote sensing; occupancy changes; degradation.